Analisa Pendekatan Pengembangan Fithrah Manusia dalam Pendidikan Islam - Zaini, Moh.; Ulum, Bachrul; Kusmawati, Wiwik; Siska Sari, Reno (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2024)
The reference sources used rely on verses of the Qur'an, alHadith, as well as the views and analyses of scientists about fithrah. Allah Swt. commands humans to always (remain on) His fithrah. Likewise, Rosulullah mentioned that no one is born (to the earth) except in a state of bringing fithrah (tawhid). This paper focuses on the 'fundamental' concept of fithroh in Islamic education, as well as the approach and follow-up of fithroh development in PAI. This research uses a type of literature research, analysing related variables or issues that are researched through notes, papers, books, news, articles and public journals. Furthermore, analysing the content, and describing in depth. The results showed that fithroh as the best gift, which is instilled into humans, from which humans have great opportunities and opportunities in developing themselves for worldly and ukhrowi interests. Approach efforts that can be done: philosophical approach, social approach, functional approach, chronological approach, - and followed up in 2 ways: 1. provide access to fithrah, 2. instil the value of Islamic education through internal approach and external approach.